A Study on the Effectiveness of Internet Advertisements - Srivastava, Vinita; Mishra, Sanjeev Kumar (Indian Journal of Marketing, 2012)
Online advertising is the means of promoting a product on the Internet using various Internet features. With the arrival of the Internet, the business world has become digitalized, and people prefer to buy stuff online, which is easier and faster. Online advertising, otherwise known as e-advertising, gives a new dimension and unique charm to the product, which is an added advantage. The primary benefit of online advertising over traditional form of advertising is that it surpasses all geographical boundaries, which cannot be gained locally. This leads to great progress in business, which is the ultimate aim of any businessman. Online advertising offers a wide spectrum of recognition, which is incomparable to any other mode of advertising. Online advertising has no time limitations and can be viewed day and night throughout the globe. It also reduces the transaction cost and contributes to the profit of the company and is secure in competition against international marketing. The owner is much more satisfied because a secure business is more beneficial and reliable. Certainly, online advertising is one step ahead over others, and helps to keep pace with the fast-changing world.